Validitas Website Fisika Berbasis Kearifan Lokal Egrang untuk Melatihkan Literasi Sains Peserta Didik SMA - Pratami, Riza Azizah; Kholiq, Abd (Universitas Negeri Surabaya, 2024)
Abstract Education today requires skills in learning, not just knowledge. One of the skills that students must have is scientific literacy skills with three aspects, namely explaining scientific phenomena, teaching and designing discussions scientifically, and interpreting data scientifically. Current educational developments go hand in hand with technological developments. The rapid development of technology means that many students are starting to forget local wisdom such as traditional games that were often played in the past. So the physics website development research that has been carried out aims to produce a website with the local wisdom of the traditional stilt game to train students' scientific literacy skills with material on the balance of rigid bodies that is valid for use in learning. This research is a type of development research using the Waterfall model with four stages used, namely Analysis, Design, Implementation, and Testing. Data collection techniques for website validity are reviewed from the language, media and material aspects. The research results showed that the percentage of validity of web-kalisa in the stilt game to train scientific literacy skills in the media aspect was 93.18%, in the material aspect it was 94.64%, and the language aspect obtained a score of 93.75%. The average validity score obtained was 93.86% in the very valid category. In this way, the resulting physics website based on local stilt wisdom is valid for use to train students' scientific literacy skills. Keywords: website, local wisdom, stilts, scientific literacy.